HEIGHTS-IE: Higher education institutions generating holistic and transferable solutions-innovation ecosystems, Philippines - Francis Mark A. Quimba; Abigail E. Andrada; Mark Anthony A. Barral (Philippine Institute for Development Studies (PIDS), 2024)
The paper examines the role of higher education institutions (HEIs) in the agribusiness innovation ecosystem in Central Visayas, Philippines, underlining their contributions, the challenges the faced, and the opportunities. Using a mix-methods approach, the research reveals that HEIs serve as knowledge sharers and collaborators within the ecosystem. Their impact, however, is limited by inadequate funding, lack of entrepreneurial engagement, among others. The agribusiness innovation ecosystem is perceived by stakeholders as nascent yet growing industry, with potential for significant economic contributions. The study further identifies areas for improvement, such as policy enhancement, deeper collaboration and engagement, and supportive intellectual property frameworks. The paper recommends strengthening HEI involvement in the agribusiness innovation to boost their role in driving regional economic growth and in addressing emerging issues like climate change and food security.
Keywords: 330; agribusiness; agribusiness innovation ecosystem; capacity building; entrepreneurship; food security; higher education institutions; intellectual property; knowledge sharing; regional development; research and development; sustainable agriculture